2001
DOI: 10.1091/mbc.12.6.1859
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Activates Cell Motility of v-Src-transformed Cells via Ras-Mitogen–activated Protein Kinase and Phosphoinositide 3-Kinase-Akt in a Tumor-specific Manner

Abstract: We investigated the production of hyaluronan (HA) and its effect on cell motility in cells expressing the v-src mutants. Transformation of 3Y1 by v-src virtually activated HA secretion, whereas G2A v-src, a nonmyristoylated form of v-src defective in cell transformation, had no effect. In cells expressing the temperature-sensitive mutant of v-Src, HA secretion was temperature dependent. In addition, HA as small as 1 nM, on the other side, activated cell motility in a tumor-specific manner. HA treatment strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 45 publications
3
64
1
Order By: Relevance
“…Thus, CD44 cross-linking via matrix components may well be the initial trigger for activation of antiapoptotic molecules (10), which proceeds via CD44v6. Activation of PI3K via CD44 has repeatedly been reported (39)(40)(41). Although we did not observe a direct association between CD44 and PI3K, this does not exclude PI3K activation by downstream signals of CD44.…”
Section: Cd44v and Apoptosis Protectioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Thus, CD44 cross-linking via matrix components may well be the initial trigger for activation of antiapoptotic molecules (10), which proceeds via CD44v6. Activation of PI3K via CD44 has repeatedly been reported (39)(40)(41). Although we did not observe a direct association between CD44 and PI3K, this does not exclude PI3K activation by downstream signals of CD44.…”
Section: Cd44v and Apoptosis Protectioncontrasting
confidence: 81%
“…We hypothesize that CD44 engagement in ASML cells triggers a CD44-PTK association and PTK activation. Such associations have repeatedly been shown for CD44/CD44v (39,40,43,44) and could be shown for ASML wt but not ASML-CD44v rsc cells. We noted an increased association between CD44v6 and c-Src in ASML cells, which was accompanied by increased activation of the focal adhesion kinase, 5 which can trigger PI3K activation.…”
Section: Cd44v and Apoptosis Protectionsupporting
confidence: 58%
“…In our study, ACC-MESO-1/OPN cells which showed an enhanced adhesion to HA obtained multidrug resistance, and a disruption of HA-CD44 interaction by siRNA or neutralizing anti-CD44 antibody abrogated the resistance to apoptosis. Several groups have revealed that HA activates the PI3K-Akt signaling pathway through CD44, thereby promoting cell survival (Sohara et al, 2001;Ghatak et al, 2002;Zoltan-Jones et al, 2003). In fact, hyaluronan oligomers (oHA), which compete for endogenous polymeric HA, suppresses the PI3K/Akt cell survival pathway and retains chemosensitivity to anti-cancer agents (Cordo Russo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As the Akt pathway is a well-characterized kinase that promotes cellular survival and several researchers have already shown that HA activates the PI3k-Akt signaling pathway (Sohara et al, 2001;Ghatak et al, 2002;Zoltan-Jones et al, 2003), we therefore investigated whether the survival signal emanating from the HA-CD44 interaction is mediated by the activation of the Akt pathway. To assess Akt phosphorylation, immunoblotting with anti-Akt and phospho-Akt-specific antibodies was carried out in ACC-MESO-1/OPN and ACC-MESO-1/Neo cells ( Figure 6a).…”
Section: Cd44-mediated Resistance To Apoptosis Involves the Akt Survimentioning
confidence: 99%
“…24 2) Likewise, exogenously added hyaluronan stimulates cell motility in transformed fibroblasts via Ras and PI3 kinase/Akt pathways. 25 These results imply that hyaluronan acts in these systems by interacting with unoccupied hyaluronan receptors or other binding proteins on the cell surface that transmit signaling information into the cell. Importantly, they also indicate that retention of hyaluronan at the cell surface by the hyaluronan synthases contributes negligibly to tumor growth.…”
Section: Hyaluronan In Tumor Cell Growth and Survivalmentioning
confidence: 98%